17-β Estradiol up-regulates energy metabolic pathways, cellular proliferation and tumor invasiveness in ER+ breast cancer spheroids - Pacheco-Velázquez, Silvia Cecilia; Ortega-Mejía, Ingrid Itzayanna; Vargas-Navarro, Jorge Luis; Padilla-Flores, Joaquín Alberto; Robledo-Cadena, Diana Xochiquetzal; Tapia-Martínez, Gabriela; Peñalosa-Castro, Ignacio; Aguilar-Ponce, José Luis; Granados-Rivas, Juan Carlos; Moreno-Sánchez, Rafael; Rodríguez-Enríquez, Sara (Frontiers in Oncology, 2022)
Several biological processes related to cancer malignancy are regulated by 17-β estradiol (E2) in ER+-breast cancer. To establish the role of E2 on the atypical cancer energy metabolism, a systematic study analyzing transcription factors, proteins, and fluxes associated with energy metabolism was undertaken in multicellular tumor spheroids (MCTS) from human ER+ MCF-7 breast cancer cells. At E2 physiological concentrations (10 and 100 nM for 24 h), both ERα and ERβ receptors, and their protein target pS2, increased by 0.6-3.5 times vs. non-treated MCTS, revealing an activated E2/ER axis. E2 also increased by 30-470% the content of several transcription factors associated to mitochondrial biogenesis and oxidative phosphorylation (OxPhos) (p53, PGC1-α) and glycolytic pathways (HIF1-α, c-MYC). Several OxPhos and glycolytic proteins (36-257%) as well as pathway fluxes (48-156 %) significantly increased being OxPhos the principal ATP cellular supplier (>75%). As result of energy metabolism stimulation by E2, cancer cell migration and invasion processes and related proteins (SNAIL, FN, MM-9) contents augmented by 24-189% vs. non-treated MCTS. Celecoxib at 10 nM blocked OxPhos (60%) as well as MCTS growth, cell migration and invasiveness (>40%); whereas the glycolytic inhibitor iodoacetate (0.5 µM) and doxorubicin (70 nM) were innocuous. Our results show for the first time using a more physiological tridimensional cancer model, resembling the initial stages of solid tumors, that anti-mitochondrial therapy may be useful to deter hormone-dependent breast carcinomas.